2017
DOI: 10.1038/s41598-017-08546-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of oxidative modification of proteins related to ATP synthesis in the left ventricles of hamsters with cardiomyopathy

Abstract: Inflammation enhanced by accumulation of reactive oxygen species plays an essential role in the progression of cardiovascular diseases. Using the 2D-oxyblot analysis and 2D-difference image gel electrophoresis (2D-DIGE), we compared the levels of ROS-induced carbonyl modification of myocardial proteins in the whole left ventricles between 6-week-old hamsters with dilated (TO-2) and hypertrophic cardiomyopathy (Bio14.6) and control hamsters (F1B). Then, 2D electrophoresis combined with MALDI-TOF/TOF tandem mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Since the effect of NE was mitigated by MAO inhibitors, it is most likely due to the reactivity of MAO-derived byproducts. Numerous oxidative post-translational modifications of the ATP synthase have been reported to affect ATP synthase efficiency (32,62,65). Using the APBA resin to pull down catechol-modified proteins, our proteomic analysis confirmed that multiple isoforms of ANT and ATP-synthase are, indeed, potential targets of catecholaldehydes (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Since the effect of NE was mitigated by MAO inhibitors, it is most likely due to the reactivity of MAO-derived byproducts. Numerous oxidative post-translational modifications of the ATP synthase have been reported to affect ATP synthase efficiency (32,62,65). Using the APBA resin to pull down catechol-modified proteins, our proteomic analysis confirmed that multiple isoforms of ANT and ATP-synthase are, indeed, potential targets of catecholaldehydes (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…This protective effect has been already described in budding yeast in which the capacity to survive elevated oxidative stress is sensitive to cytoplasmic actin dynamics though the exact process involved is still unknown . Under pathological conditions, several sources of ROS lead to deleterious oxidative stress in the cardiac muscle, such as mitochondrial respiratory chain dysfunction and monooxygenase enzymes . So, is α‐cardiac actin able to reduce oxidative stress by impacting on these sources of ROS?…”
Section: Discussionmentioning
confidence: 92%
“…53,54 Under pathological conditions, several sources of ROS lead to deleterious oxidative stress in the cardiac muscle, such as mitochondrial respiratory chain dysfunction and monooxygenase enzymes. [55][56][57][58] So, is α-cardiac actin able to reduce oxidative stress by impacting on these sources of ROS? At first, we demonstrated that maintaining α-cardiac actin preserves the alignment of mitochondrial network and the global aspect of these organelles.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that biomolecule oxidation is closely linked to a series of pathological events; the accumulation of redox-dependent posttranslational modification of certain key proteins would lead to ER stress and subsequent activation of the mitochondrial apoptotic pathway. The heart is one of the highest ATP-consuming organs and most of ATP is generated by the mitochondria through primarily oxidative phosphorylation [ 34 38 ]. Furthermore, network analysis has suggested that ADR-caused heart damage is majorly caused by impaired protein folding due to oxidative stress and mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%